2003
DOI: 10.1176/appi.ps.54.8.1155
|View full text |Cite
|
Sign up to set email alerts
|

A Program for Managing Weight Gain Associated With Atypical Antipsychotics

Abstract: This study assessed the efficacy of a weight control program for patients taking atypical antipsychotics. Thirty-one patients with schizophrenia or schizoaffective disorder participated in a 12-week weight control program that incorporated nutrition, exercise, and behavioral interventions. Changes in patients' weight and in body mass index (BMI) were recorded and compared with those of 15 patients in a control group. The intervention group had a mean weight loss of 2.7 kg (six pounds) and a mean reduction of.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
111
1
5

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(120 citation statements)
references
References 6 publications
3
111
1
5
Order By: Relevance
“…However, the average weight loss in these ten studies varied by study design. The mean weight loss for the three single-group studies (20,31,24) was 8.2±5 pounds, whereas the three quasi-experimental studies (24,25,28) and four randomized controlled trials (2123,35) showed more modest average weight loss (6.2±.4 pounds and 3.4±2.9 pounds, respectively). The mean for the randomized controlled trials reviewed falls below the mean weight loss reported in meta-analyses of randomized controlled trials of lifestyle interventions tested in the general population, which was eight to 11 pounds (44,45).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…However, the average weight loss in these ten studies varied by study design. The mean weight loss for the three single-group studies (20,31,24) was 8.2±5 pounds, whereas the three quasi-experimental studies (24,25,28) and four randomized controlled trials (2123,35) showed more modest average weight loss (6.2±.4 pounds and 3.4±2.9 pounds, respectively). The mean for the randomized controlled trials reviewed falls below the mean weight loss reported in meta-analyses of randomized controlled trials of lifestyle interventions tested in the general population, which was eight to 11 pounds (44,45).…”
Section: Discussionmentioning
confidence: 91%
“…Four studies did not specify medication inclusion criteria, but they did enumerate in a general manner (for example, second-generation antipsychotic medications) the type of medications that participants were taking at the time of enrollment (18,23,30,33). The rest of the studies specified medication inclusion criteria that were either restricted to monotherapy with one antipsychotic medication at the time of enrollment (26,27) or combination treatment of one antipsychotic with other psychotropics (16,20,21,24,25,31,32,36). Three studies restricted their intervention to patients taking olanzapine (17,19,22).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a meta-analysis on randomised, controlled, cognitive-behavioural weight loss trials, Bonfioli et al (2012) concluded that in patients with psychosis, a weight loss of 0.98 points in BMI (corresponding to a loss of 3.12% of initial weight) was demonstrated from pooled data. Weight loss programs can also prevent weight gain associated with antipsychotic use and even promote weight loss (Chen et al, 2009, Gabriele et al, 2009, Menza et al, 2004, Vreeland et al, 2003. In a study by Zhang et al (2012), patients with psychotic spectrum disorders experienced a greater percent baseline weight loss at 12 months, and greater percent BMI loss at 9 and 12 months than people suffering from other psychiatric disorders and no psychiatric disorder.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Although weight control programs have been tested in this population, few experimentally evaluate PA interventions, and many only address diet and nutrition (McDevitt et al, 2005;Littrell et al, 2003;McCreadie et al, 2005;Evans et al, 2005;Menza et al, 2004). When PA is addressed, studies typically measure it using simple self-reports of time engaged in PA, usually walking (Vreeland et al, 2003). Recently, however, there have been a few reports assessing the reliability and validity of PA self-report measures in persons with SPMI.…”
Section: Introductionmentioning
confidence: 99%